2021
DOI: 10.3390/molecules26134100
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/AKT/mTOR Signaling Pathway in Lung Cancer: An Update Regarding Potential Drugs and Natural Products

Abstract: Lung cancer is one of the most common cancers and has a high mortality rate. Due to its high incidence, the clinical management of the disease remains a major challenge. Several reports have documented a relationship between the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway and lung cancer. The recognition of this pathway as a notable therapeutic target in lung cancer is mainly due to its central involvement in the initiation and progression of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 211 publications
(237 reference statements)
0
81
0
Order By: Relevance
“…Activation of the oncogenic PI3K/AKT/mTOR pathway mediates tumorigenesis and resistance to EGFR TKIs in NSCLC 1619 . Since PDK1 represents a pivotal node in this important signaling axis, we analyzed the phosphorylation status of its major signaling effectors in NCI-H1975, NCI-H1975/OSIR, H1975-OsiR-PDK-/- and H1975-OsiR-PDK1++/++ clones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the oncogenic PI3K/AKT/mTOR pathway mediates tumorigenesis and resistance to EGFR TKIs in NSCLC 1619 . Since PDK1 represents a pivotal node in this important signaling axis, we analyzed the phosphorylation status of its major signaling effectors in NCI-H1975, NCI-H1975/OSIR, H1975-OsiR-PDK-/- and H1975-OsiR-PDK1++/++ clones.…”
Section: Resultsmentioning
confidence: 99%
“…PDK1 is a pivotal node in the oncogenic PI3K/AKT/mTOR pathway 20,21 , which mediates tumorigenesis and resistance to EGFR tyrosine kinase inhibitors in NSCLC 1619 . Osimertinib had no effect on AKT expression levels, which was similar in both PDK1 knock out and overexpressing clones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current commercially accessible targeted inhibitors for cancer patients with abnormal activation of the PI3K/AKT/mTOR pathway include everolimus (mTOR inhibitor), sirolimus (mTOR inhibitor), temsirolimus (mTOR inhibitor), alpelisib (PI3K inhibitor), duvelisib (PI3K inhibitor), copanlisib (PI3K inhibitor), idelalisib (PI3K inhibitor), umbralisib (PI3K inhibitor). Phase III clinical trials of AKT inhibitors, such as capivasertib and ipatasertib, have been proceeded in cancer ( Figure 1 and Table 1 ) ( 6 , 16 , 17 ). Preclinical and clinical trials have shown encouraging outcomes for these targeted medicines.…”
Section: Introductionmentioning
confidence: 99%
“…As we all known, PI3K/AKT signaling pathway has been widely reported to be one of the most common and important pathways for cancers [34][35][36]. The pathway includes multiple core components and is controlled at multiple levels.…”
Section: Discussionmentioning
confidence: 99%